The Representations, the Meanings and the “Beat” of Bumba-Meu-Boi Festivities, from Maranhão, and Boi-Bumbá Festivities, from Middle Amazonas State and Parintins - Silva, Zélia Lopes da (Advances in Social Sciences Research Journal, 2022)
Festivals nowadays allow diverse approaches considering the multiple meanings they can bear, even in the conjunction of a globalized world, marked by rapid technological transformations that make national borders increasingly frayed. In this context, the quest to preserve the cultural manifestations that ensure meaning to social relations is recurrent, considering that such transformations inscribe their signs all over the world. Following these concerns, we will investigate the festivals of the Cultural Complex of Bumba-Meu-Boi, from Maranhão (an intangible cultural heritage of Brazil and of humanity) and the Cultural Complex of Boi-Bumbá from Middle Amazonas State and Parintins. These cultural expressions were inscribed, in the 21st century, in the Registry Book of Celebrations of IPHAN – Institute of National Artistic and Historical Heritage, as national intangible cultural heritage. Such recognition is due to the fact that these festivities express aspects of Catholic popular culture and religiosity that carry beliefs of African origin, of black people and the cultural traditions of the “native” or “forest” peoples (named indigenous by white people), which are referenced as elements of affirmation of caboclo and national identity, as a result of this origin. For these reflections, we will use the official dossiers and documents that were the basis for the inscription of these festive expressions in the aforementioned Book, photos, videos, as well as in the “Constitution of the Federative Republic of Brazil” and in the specialized, theoretical and historiographical bibliography.